Adverse events in the paediatric emergency department: a prospective cohort study. Issue 3 (29th April 2020) - Plint, Amy C; Stang, Antonia; Newton, Amanda S; Dalgleish, Dale; Aglipay, Mary; Barrowman, Nick; Tse, Sandy; Neto, Gina; Farion, Ken; Creery, Walter David; Johnson, David W; Klassen, Terry P; et al.
Abstract : Background: Understanding adverse events among children treated in the emergency department (ED) offers an opportunity to improve patient safety by providing evidence of where to focus efforts in a resource-restricted environment. Objective: To estimate the risk of adverse events, their type, preventability and severity, for children seen in a paediatric ED. Methods: This prospective cohort study examined outcomes of patients presenting to a paediatric ED over a 1-year period. The primary outcome was the proportion of patients with an adverse event (harm to patient related to healthcare received) related to ED care within 3 weeks of their visit. We conducted structured telephone interviews with all patients and families over a 3-week period following their visit to identify flagged outcomes (such as repeat ED visits, worsening symptoms) and screened admitted patients' health records with a validated trigger tool. For patients with flagged outcomes or triggers, three ED physicians independently determined whether an adverse event occurred. Results: Of 1567 eligible patients, 1367 (87.2%) were enrolled and 1319 (96.5%) reached in follow-up. Median patient age was 4.34 years (IQR 1.5 to 10.57 years) and most (n=1281; 93.7%) were discharged. Among those with follow-up, 33 (2.5%, 95% CI 1.8% to 3.5%) suffered an adverse event related to ED care. None experienced more than one event. Twenty-nine adverse events (87.9%, 95% CI 72.7% to 95.2%) were deemed preventable. The most common types of adverse events (not mutually exclusive) were management issues (51.5%), diagnostic issues (45.5%) and suboptimal follow-up (15.2%). Conclusion: One in 40 children suffered adverse events related to ED care. A high proportion of events were preventable. Management and diagnostic issues warrant further study.